Microfluidic devices for multiplexed detection of foodborne pathogens. (May 2021) - Han, Xiaoying; Liu, Yuanhui; Yin, Juxin; Yue, Min; Mu, Ying
Graphical abstract: This graph illustrates "sample in to answer out" detection procedure of foodborne pathogens. Food samples were first processed into detectable molecules in sample preparation process, and then the corresponding detection methods were applied to form qualitative or quantitative readouts. The results can be obtained directly or analyzed with other equipment. In this review, recent developments of sample preparation and detection methods were exhaustively illustrated, and their limitations and advantages were also summarized to give a comparative assessment for future investigation to ensure food safety. Highlights: Microfluidics fulfill rapid, sensitive and automatic on-site detection. Multiplexed detection is highly demanded in microbiological surveillance. Various detection and the corresponding sample preparation methods were discussed. Abstract: The global burden of foodborne diseases is substantial and foodborne pathogens are the major cause for human illnesses. In order to prevent the spread of foodborne pathogens, detection methods are constantly being updated towards rapid, portable, inexpensive, and multiplexed on-site detection. Due to the nature of the small size and low volume, microfluidics has been applied to rapid, time-saving, sensitive, and portable devices to meet the requirements of on-site detection. Simultaneous detection of multiple pathogens is another key parameter to ensure food safety. Multiplexed detection technology, including microfluidic chip design, offers a new opportunity to achieve this goal. In this review, we introduced several sample preparation and corresponding detection methods on microfluidic devices for multiplexed detection of foodborne pathogens. In the sample preparation section, methods of cell capture and enrichment, as well as nucleic acid sample preparation, were described in detail, and in the section of detection methods, amplification, immunoassay, surface plasmon resonance and impedance spectroscopy were exhaustively illustrated. The limitations and advantages of all available experimental options were also summarized and discussed in order to form a comprehensive understanding of cutting-edge technologies and provide a comparative assessment for future investigation and in-field application.